Digital Marketing and Sales Performance Perceptions among Rural MSMEs: A Study in Sawang District, North Aceh - Ameliany, Nanda; Sufi, Sufi; Iryani, Lisa; Isma, Yuli Santri; Hakiki, Nur (SAFE-Network, 2025)
In an increasingly digital economy, many micro, small, and medium enterprises (MSMEs) face challenges in adapting their marketing strategies to remain visible and competitive, particularly in rural or underserved regions. This study investigates how MSMEs in Sawang District, North Aceh Regency, experience and perceive the impact of digital marketing on their sales performance. Using a quantitative descriptive approach, data were collected through structured questionnaires and analyzed using regression techniques to explore the association between digital marketing efforts and perceived business outcomes. The findings reveal a consistent positive relationship, suggesting that MSMEs that actively utilize digital tools—such as social media, websites, and online search platforms—tend to report more favorable assessments of their sales performance. Although both variables were assessed through self-reported measures, and therefore reflect perception rather than objective data, the results offer meaningful insight into how digital engagement shapes entrepreneurial confidence and strategic behavior. This underscores the importance of digital literacy, content effectiveness, and platform accessibility in empowering small businesses. The study recommends enhanced support through policy initiatives, training programs, and digital infrastructure to strengthen MSME capacity. Future research should consider integrating perceptual and objective indicators to more comprehensively assess the role of digital marketing in business development.